A new EABC for DC-link capacitor voltage equalisation of MPC-based 5-L HPFC. (23rd April 2020) - Yalla, Naveen; Agarwal, Pramod
In this paper, a new multi-device unidirectional buck boost topology is proposed to equalise the DC link capacitor voltages of multi-point clamped (MPC)-based five-level high power factor (HPF) converter. Two independent controlled chopper topologies (consisted with two parallel connected control devices and one single unidirectional diode). The proposed topology effectively and efficiently to mitigate the deviation of DC link capacitor voltages, which is caused due to voltage drift phenomena. The desired PWM signals are generated by a phase shift control strategy. Proposed configuration provides two times ripple frequency current through the inductor, which can contribute to less inductor size 'all most 50% of traditional one' and therefore lesser weight of the core and its corresponding losses. The contribution of proposed topology is analysed mathematically and results are verified by simulation as well as prototype experimental setup.